Determinación del tiempo letal 50 por inmersión de dysmicoccus brevipes ckc y su control en racimos con productos orgánicos - Carrazco Espinoza, Vicente Mauricio (2006)
With the beginning of the export of organic banana tree to Japanin the year 2005, in the laboratory of Entomology of the company Celia Maria you work with formulations made up of barbasco extracts, pepper and other ingredients to evaluate the effectiveness in the cochineal control in front of in front of two vegetable oleatos Cochibiol and Protec K. and to determine the time required to kill to colonies of cochineals for immersion. te outlined objectives wereTo determine TL50 (lethal time 50) for Dysmicoccus brevipes Ckl for immersion in emulsions of soap potásicos and organic insecticideTo compare the effectiveness of Protec K soap potásicos with a formulation of organic insecticide in the cochineal control in banana tree clusters in the phase of the crop.Four formulations of extracts of Barbasco-pepper were rehearsed with different proportions of the basic component and of other ingredients and two vegetable oleatos Cochibiol and Protec K.The products were applied to recently harvested healthy clusters in having infested by the plague, when they remained in having hung in the funicular one, after the glide of the product with paintbrushes you proceeded to retire cochineal specimens to transfer them to plates petra with bottom of paper napkin target. This activity was carried out in four shipments in the weeks 16, 17, 19 and 20. After evaluating the effectiveness, it was selected to the formulation F4, Cochibiol and Protec K for the realization of the tests of mortality for immersion.The statistical analyses of the mortality in the tests were carried out at random by means of the mathematical pattern of the Design blocks with five repetitionsThe results obtained in the field, were satisfactory in the sense that the mortality of the cochineal evaluated to the three days demonstrates that none of the treatments offers the total control of a population, the best index of corrected mortality varies among 83 to 87% with the formulation F4 to 5%, Cochibiol 1.5% and Protec K 1%.In the immersion tests the levels of mortality went inferior to those of field, due to the overlapping of individuals in the yolks of the tubers, that which impeded the penetration of the experimental products. The maximum reached mortality was of 50.4% with the formulation of barbasco-pepper, Cochibiol and Protec K.